1992
DOI: 10.1111/j.1559-1816.1992.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Experience of Stress Following the Birth of a First Child: Identification of Stressors and Coping Resources1

Abstract: The purpose of this study is to identify, through a retrospective methodology, stressor and coping resource variables which are involved in mothers' experience of stress one month after the birth of a first child. The variables were identified on the basis of previous work in this field, and were categorized as stressor or coping resource variables according to the writmgs of authors in the larger domain of stress and coping. The influence of interactive and additive combinations of stressors and coping resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
15
0
6
Order By: Relevance
“…Use of short assessment tools such as the PSI/SF could be used during a normal postpartum visit to the physician or nurse practitioner. Tessier andcolleagues (1992, p. 1334) assert that "resource building" in the prenatal period will benefit the infant after birth and that it is not the birth of baby, nor the daily stressors that are most significant in the process of stress for the new mother, but the personal and social resources as perceived by the mother that determines her level of stress. This is validated by Belsky's (1984) belief that it is the parenting contribution that is the most effective determinant of parental functioning.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Use of short assessment tools such as the PSI/SF could be used during a normal postpartum visit to the physician or nurse practitioner. Tessier andcolleagues (1992, p. 1334) assert that "resource building" in the prenatal period will benefit the infant after birth and that it is not the birth of baby, nor the daily stressors that are most significant in the process of stress for the new mother, but the personal and social resources as perceived by the mother that determines her level of stress. This is validated by Belsky's (1984) belief that it is the parenting contribution that is the most effective determinant of parental functioning.…”
Section: Discussionmentioning
confidence: 98%
“…However, research has revealed that becoming a mother can be a stressful experience and more complex than previously thought. Many factors are related to the development of parenting stress including social support (Gage & Christensen, 1991;Levy-Shiff et al, 1998); self-efficacy (Lutenbacher, 2002;Reece & Harkless, 1998); personality (Belsky, Crnic, & Woodworth, 1995;Mulsow et al, 2002;Younger, 1991); cognitive appraisal and every day stressors (Levy-Shiff et al, 1998;Tessier et al, 1992), and infant temperament, difficulty, birth weight and sleep patterns (Becker, Chang, Kameshima, & Bloch, 1991;Gelfand et al, 1992;Halpern, Brand, & Malone, 2001;Pridham, Chang, & Chiu, 1994;Secco & Moffatt, 2003;Terry, 1991). The mother's perception of stress and the degree of role ambiguity in the mothering role also may affect the mother's transition to parenthood (Gage & Christensen, 1991;Reece & Harkless, 1998).…”
Section: Review Of Literaturementioning
confidence: 97%
See 2 more Smart Citations
“…During the first postpartum year, most parents complete the major developmental tasks associated with their parental roles and usually do so relatively well (Eagan, 1985;Kalmuss et al, 1992;Mercer, 1990). The psychological upheavals associated with the transition to parenthood are generally transitory and of modest intensity, and most parents progressively cope with the many demands of this stage without major difficulties (Campbell et al, 1992;Mercer, 1985;Tessier et al, 1992;Terry, 1991). However, in a high-risk pregnancy context, this period of psychological instability may last longer and be more intense.…”
Section: Transition To Parenthood Stress and Distressmentioning
confidence: 95%